Bootstrapping in small firms: An empirical analysis of change over time - Ebben, Jay; Johnson, Alec (Journal of Business Venturing, 2006)
While bootstrapping is widely utilized as a strategic practice of small firms and has been regarded in the entrepreneurship literature as an important topic of study, little has been done to link bootstrapping to organizational theory. This paper presents hypotheses and an empirical study regarding bootstrapping and organizational development for small firms. The results of the study indicate that different types of bootstrapping are utilized at different periods in the life of a small firm, and that the methods utilized coincide to some extent with organizational theory predictions.